THE MATHEMATICAL MODEL OF THE ESSENTUKI'S MINERAL WATERS DEPOSIT - Michael Maksimovich Mardoyan (Современная наука и инновации, 2022)
The article deals with the problems arising from the exploitation of mineral waters deposits in the KMV region,the necessity for mathematical modeling in determining rational modes of mineral waterresources exploitation is indicated, and a mathematical model of the deposit site is given.